Implementasi Peraturan Bank Indonesia tentang Risiko Pembiayaan Bank Syariah Indonesia (BSI) di Demak - Kusrini, Eni (TAWAZUN: Journal of Sharia Economic Law, 2023)
Risk management is crucial in organizing and implementing decision-making rules regarding customer financing. The analysis of all decisions made by the bank must be carefully planned and managed to avoid a higher incidence of non-performing loans, especially if the characteristics of consumers are not thoroughly observed, which is a part of the business unit facing management problems/risks such as murabahah financing. Risks arise due to dishonesty and economic difficulties of customers in transactions. Leaders, bank managers, and all divisions of the bank are expected to have the ability to reduce risks to achieve maximum profit orientation. The existing problems can be analyzed in terms of credit risk and liquidity risk regarding decision-making by management, the sequence of assets, and liabilities that must be considered to minimize emerging risks. The research method used is the qualitative descriptive approach. The results of this study show that the credit risk management applied by BSI in Demak is capable of setting limits on the losses of a market-risky transaction. PT. BSI KCP Demak, in relation to liquidity risk, strives for regular payments for consideration of existing exchange rates, thus being able to condition and meet customer financing demands.